HIKMAH ADANYA AYAT MUTASYABIHAT - Sairi Sairi; Syabri Syabri; Muhammad Sapitra (CV. Adiba Aisha Amira, 2022)
The Qur'an is a guide for mankind that lays the principal foundations in all matters of life and is a universal book, which is the main foundation of Muslims and a way of life for its adherents. This study has its own procedure so that it is considered that there is no difference in making scientific papers. According to Zed, (2008) the library method should not be underestimated, because this method is also a method that not only collects related theories but also analyzes the theoretical studies carried out. The details are caused by three things, namely: because of the ambiguity in pronunciation, in meaning, and in pronunciation and meaning. The mutasyabih verses require more efforts to reveal their meaning by being more active in studying, diligently studying so as to increase the reward for those who study them. is as opposed to the word muhkam, namely the verses of the Qur'an which contain ambiguity and complexity in understanding them. Allah sent down mutasyabihat verses to show their greatness, and to show humans to think and reveal their secrets. happens wisely, namely with mutual respect